Symptomatic splenogonadal fusion with splenic torsion in an adolescent female - J. Guzman; M.M. Wieck (Elsevier, 2022)
Splenogonadal fusion is a rare entity found predominantly in males and often asymptomatic or mildly symptomatic. Here we report a case of symptomatic splenogonadal fusion in a female. She presented with abdominal pain and was found to have splenic torsion that required operative detorsion and partial splenectomy. We further review outcomes and prognosis of this benign condition in males which suggest that the abnormal ovary should be preserved in females with this rare anomaly.